(3cJGH deMjj GdOjf Hf GdYQHis - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3GSJNQJ Gddg JYGdi hbjOJ ai gPG GdLRA eG JVefg ef GdCHjGJ GdZRdjI HecI JjefkG eG hbY ai SfI EMOi YTQI hSJeGjI dGZjQ s
(3BNQgG (B:s
(3eG UObJ QjM GdUHG MOjK CJJ HGdNOY bO JcPH GdQjM EPG JSeY eGde JSeY s
(3GdfSNI HgG MhGTs
(3hgh YHGQI Yf eLehYI bUGFO OjfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281s
(3eUOQ GbJfGA GdCUd (B:s
(3GdXGgQjI (B(9332) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs